2014
DOI: 10.1111/boj.12167
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetics and taxonomy of the New World leafy spurges,EuphorbiasectionTithymalus(Euphorbiaceae)

Abstract: The 480 species of leafy spurges, Euphorbia subgenus Esula, represent the main temperate radiation in the large genus Euphorbia. This group is distributed primarily in temperate Eurasia, but with smaller, disjunct centres of diversity in the mountains of the Old World tropics, in temperate southern Africa and in the New World. The majority of New World diversity (32 species) occurs in a single section, section Tithymalus. We analysed sequences of the nrITS and plastid ndhF, trnH-psbA, trnS-trnG and trnD-trnT r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Recently, Geltman et al (2014) recognized that E. virgata has been erroneously treated as E. esula s. str. in North America, and that the later has never been widespread in North America (Peirson et al 2014). E. esula s. str.…”
mentioning
confidence: 98%
“…Recently, Geltman et al (2014) recognized that E. virgata has been erroneously treated as E. esula s. str. in North America, and that the later has never been widespread in North America (Peirson et al 2014). E. esula s. str.…”
mentioning
confidence: 98%
“…ex Rchb. (Peirson et al 2014). The same study further verified the presence four clades in Euphorbia and indicated that E. subgen.…”
Section: Researchmentioning
confidence: 57%
“…Helioscopiae (annuals). According to recent phylogenetic studies on subgenus Esula using DNA sequence data (Kryukov et al 2010, Barres et al 2011, Frajman and Schönswetter 2011, Peirson et al 2014), it is clear that life history in subgen. Esula is not phylogenetically stable and thus not a reliable character for infrageneric classification.…”
Section: Resultsmentioning
confidence: 99%